2020
DOI: 10.1002/cne.25070
|View full text |Cite
|
Sign up to set email alerts
|

Morphological identification of thoracolumbar spinal afferent nerve endings in mouse uterus

Abstract: Major sensory innervation to the uterus is provided by spinal afferent nerves, whose cell bodies lie predominantly in thoracolumbar dorsal root ganglia (DRG). While the origin of the cell bodies of uterine spinal afferents is clear, the identity of their sensory endings has remained unknown. Hence, our major aim was to identify the loca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…In any case, the present study replicated a separate finding from the rat, in that CGRPexpressing nerve fibers were intrinsically more concentrated within the cranial region of the uterine horn, compared to the middle and caudal portions (Zoubina et al, 1998). Use of CGRP as a sensory marker is in line with our recent study that identified spinal afferent nerve endings in the mouse uterus for the first time (Dodds et al, 2021). Other neurochemical markers that label sensory neurons (such as substance P) may reveal a different pattern innervation to the mouse uterine horn following DRG removal.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In any case, the present study replicated a separate finding from the rat, in that CGRPexpressing nerve fibers were intrinsically more concentrated within the cranial region of the uterine horn, compared to the middle and caudal portions (Zoubina et al, 1998). Use of CGRP as a sensory marker is in line with our recent study that identified spinal afferent nerve endings in the mouse uterus for the first time (Dodds et al, 2021). Other neurochemical markers that label sensory neurons (such as substance P) may reveal a different pattern innervation to the mouse uterine horn following DRG removal.…”
Section: Discussionsupporting
confidence: 91%
“…Here, we demonstrate that CGRP-expressing lumbosacral spinal afferent neurons supply relatively minor innervation across the mouse uterine horn. Subsequent retrograde neuronal tracing confirmed that few lumbosacral spinal afferent neurons innervate the caudal uterine horn, with a greater proportion arising from thoracolumbar DRG; consistent with tracing from the mid and whole uterus (Herweijer et al, 2014;Dodds et al, 2021). Collectively, these findings suggest that sensory information between the mouse uterine horn and central nervous system is primarily relayed via thoracolumbar spinal afferent neurons.…”
Section: Discussionsupporting
confidence: 60%
“…Sensory innervation to the mouse uterus is predominantly supplied by spinal afferents arising from T13-L2 DRG, with a minority arising from L6-S1 21 , 22 . The lateralisation of this organ affords the opportunity for internal controls with unilateral DRG lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the difference between the two techniques is we do not remove the DRG, once we have injected DRGs with tracers. By injecting minute quantities of neuronal tracer into single DRG, it has been demonstrated we can readily identify the nerve endings that arise from a single DRG neuron 22 , 27 , 28 . This cannot be achieved using transgenic reporter or cre-induced expression of fluorescent reporters, which label large populations of axons whose spatial fields overlap extensively; see ref.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroanatomical studies performed in rodents show sensory afferents innervating the urogenital organs and colon are predominantly peptidergic (containing substance P, calcitonin gene-related peptide) [56][57][58]. There is also strong evidence for convergence of bladder and colon sensory innervation at the level of primary afferents, and peripheral sensitization of urinary bladder and pelvic nerve afferents in the setting of colonic irritation, which potentially contribute to disorders characterized by chronic pelvic pain [57,59].…”
Section: Antinociceptive Effects In Animal Models Of Bladder Pain Syndrome and Endometriosismentioning
confidence: 99%